Inferring wildlife poaching in southeast Asia with multispecies dynamic occupancy models. Issue 2 (25th October 2019) - Marescot, Lucile; Lyet, Arnaud; Singh, Rohit; Carter, Neil; Gimenez, Olivier
Abstract : Determining the 'space race' between co‐occurring species is crucial to understand the effects of interspecific interactions on the extinction risk of species threatened by poachers and predators. Dynamic two‐species occupancy models provide a flexible framework to decompose complex species interaction patterns, while accounting for imperfect detection. These models can describe poachers–wildlife interactions, as they allow estimating occupancy, extinction and colonisation probabilities of wildlife conditional on the occurrence of poachers and vice versa. We applied our model to a case study on wildlife poaching in the eastern plains of Cambodia. We used co‐occurrence data extracted from the database of the SMART partnership to study the distribution dynamics between poachers and six ungulate species pooled together into the tiger prey guild. We used four years of survey data reporting the locations of snares and of presence signs of the ungulates recorded by rangers during their monthly multi‐patrolling sessions. Our results showed that a substantial proportion of the sites occupied by ungulate species went extinct over the years of the study while the proportion of sites colonised by poachers increased. We also showed, for the first time, that spatio‐temporal heterogeneity in the patrolling effort explains a great deal of the variation in the detection of poachers and ungulates. Our approach provides practitioners with a flexible and robust tool to assess conservation status of species and extinction risk of wildlife populations. It can assist managers in better evaluating, learning and adapting the patrolling strategies of rangers.